Infestation of fruit by conspecific and heterospecific females deters oviposition in two Tephritidae fruit fly species - Liendo, María Clara; Parreño, María Alejandra; Pietrek, Alejandro G.; Bouvet, Juan Pedro; Milla, Fabian Horacio; Vera, María Teresa; Cladera, Jorge Luis; Segura, Diego Fernando (Wiley, 2020)
Tephritidae fruit fly larvae develop entirely in the host chosen by the females. To improve the fitness of their progeny, females would benefit from rejecting previously exploited hosts. Anastrepha fraterculus and Ceratitis capitata are two species of fruit flies having similar nutritional requirements and overlapping in their distribution. Previous studies found that competition between the larvae of these species might reach high levels, suggesting that cross‐recognition would be an adaptive trait. In this work, we tested the ability of A. fraterculus and C. capitata females to recognize and avoid fruits previously infested by both conspecific and heterospecific females. In laboratory behavioural arenas, females were presented with fruits that had been previously exposed to either conspecific or heterospecific females. Then, we conducted choice and non‐choice assays to compare the response of A. fraterculus and C. capitata females to infested and non‐infested fruits. In non‐choice tests, the females from both species rejected fruits previously infested by conspecific and heterospecific individuals. However, the rejection occurred at different steps of the sequence leading to oviposition: A. fraterculus showed a lower rate of visits to infested fruits, whereas C. capitata visited both infested and non‐infested fruits, but the latency to visit a fruit and the rejection frequency were higher and the duration of the visit to infested fruit was lower. In choice assays, the rejection of heterospecific infested fruit was higher than that of conspecific infested fruits, for both species. Our results suggest that, regardless of the sensory mechanism used by females, the recognition of previous infestation is bidirectional and females of both species, belonging to different genera, recognize fruit infested by heterospecifics. These responses indicate that cross‐recognition, supposedly a highly beneficial trait, could be occurring in nature, thus reducing interspecific competition and contributing to the coexistence of these species.